Relationship between awareness, knowledge, and attitude of behavioural intention towards halal jobs among Malaysian Muslim university students - Hashim, Noor Haslihsa; Kamarulzaman, Nitty Hirawaty; Ab Rahman, Suhaimi; Othman, Mohhidin (HH Publisher, 2020)
In the emergence of global halal market, developing halal human capital with provisions of knowledge and skills are indispensable for professional efficiency in management and implementation, especially for Malaysia as the world’s leader in the halal industry. Therefore, it is important to determine the awareness among Muslim university students on job opportunities and their intentions to choose career paths in halal industry. The objectives of this study were to determine the level of Muslim university students’ awareness, knowledge, and attitude of halal jobs; and to determine the relationship between awareness, knowledge, and attitude towards behavioural intention of halal jobs. A structured questionnaire was used as a research instrument to collect responses from 1,454 final year Muslim university students in public and private universities located in the Klang Valley, Malaysia. Data were analysed using descriptive analysis and Pearson correlation. Results revealed that the Muslim university students have a high level of awareness, adequate level of knowledge, and high level of behavioural intention of halal jobs. There was also a significant but weak relationship between knowledge and attitude towards halal jobs. In addition, there was a moderate relationship observed between awareness and attitudes among Muslim university students. The present study concluded that the positive awareness, knowledge, and attitude towards halal jobs influenced significantly on their behavioural intention towards halal jobs.